2016
DOI: 10.1080/10888438.2016.1186168
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Kindergarten Spelling and Their Relations to Later Spelling Performance

Abstract: Learning the orthographic forms of words is important for both spelling and reading. To determine whether some methods of scoring children’s early spellings predict later spelling performance better than do other methods, we analyzed data from 374 U.S. and Australian children who took a 10-word spelling test at the end of kindergarten (mean age 6 years, 2 months) and a standardized spelling test approximately two years later. Surprisingly, scoring methods that took account of phonological plausibility did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 35 publications
3
23
0
1
Order By: Relevance
“…Finally, our data are in line with recent correlational and predictive studies showing that there seems to be a strong predictive role of early emergent literacy skills to subsequent reading and writing in primary school (Ouellette & Sénéchal, 2016;Treiman, et al, 2016). Thus, as it expands the development of memory connections that link phonological units to orthographic representations, invented spelling measures should be considered along with phonological awareness and letter knowledge as a valuable means of enhancing children's literacy learning (Caravolas et al, 2012;Lonigan et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, our data are in line with recent correlational and predictive studies showing that there seems to be a strong predictive role of early emergent literacy skills to subsequent reading and writing in primary school (Ouellette & Sénéchal, 2016;Treiman, et al, 2016). Thus, as it expands the development of memory connections that link phonological units to orthographic representations, invented spelling measures should be considered along with phonological awareness and letter knowledge as a valuable means of enhancing children's literacy learning (Caravolas et al, 2012;Lonigan et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…In fact, the use of partial spellings and phonologically plausible but unconventional spellings indicate that young children frequently have some knowledge regarding the connections between sounds and spellings, as found in a recent study with American and Australian kindergarteners (Treiman, Kessler, Pollo, Byrne & Olson, 2016). Furthermore, studies in Hebrew have shown that educational activities where children are invited to actively think about word spelling may enhance their own literacy learning process when supported by adults and/or more competent peers .…”
Section: The Role Of Early Literacy On Reading and Writing Achievementmentioning
confidence: 79%
“…Other spelling assessment proposals evaluate a combination of phonological and orthographic knowledge. For example, Treiman et al (2016) assessed children's spelling considering both phonographic and orthographic skills. Words spelled with all conventional letters received more points than productions that were spelled with phonologically plausible, but unconventional, letters.…”
Section: Assessing Spellingmentioning
confidence: 99%
“…There is some research systematically comparing spelling scoring metrics but no studies have done so in exploring the relation between spelling and reading comprehension. Treiman and colleagues examined the relations between spelling scoring metrics and future spelling ability (Treiman, Kessler, & Caravolas, 2019;Treiman, Kessler, Pollo, Byrne, & Olson, 2016). Even as early as the beginning of kindergarten, metrics based on accuracy of letters, such as whole-word accuracy and correct letter sequences, were better predictors of second grade spelling than phoneme-based metrics, such as phonological plausibility and phoneme distance.…”
Section: Spelling Scoring Metricsmentioning
confidence: 99%